Project management in Malaysia : strategies, techniques and implementation for project success - One Day Intensive Seminar on Project Management in Malaysia - Strategies, Techniques and Implementation for Project Success (2000 : Kuala Lumpur) (Kuala Lumpur : Asia Pacific Diligence, 2000)
36